Borderless Space - Ideas for Regional Collaboration - Leonie Janssen-Jansen; Melika Levelt (European Regional Science Association (ERSA), 2005)
Regional planning initiatives emerge in response to a growing number of land use and related issues that transcent political and jurisdictional boundaries and often involve business and non-profit organizations. Cities are no longer central is planning discussions. Urban networks reflect better the new spatial dynamics. Regional planning strategies are sought to link the public and private spheres of this urban networks action. An important starting point is to organize relations between the relevant and different governmental bodies in the multi-level and multi agency society. How can the abundance of subterritorial governmental bodies be connected, especially within the light of decentralisation processes that are going on? In addition an important question is how this public sphere can be linked to the sphere of private regional action. What are important elements in strategies of 'organizing connectivity'? Will 'pragmatic regionalism with a purpose' be an interesting strategy? In the light of this growing interest in acting regionally, this paper offers insights in motives for such regionalism. A framework to identify and promote best practices for regional collaboration, with attention for vertical as well as horizontal connectedness within the public sphere, as well as linking this public to the private sphere of regional action will be central. Several motives and principles that might be beneficiary for regional collaboration are dealt with. The case of Schiphol and Amsterdam in the Netherlands, as an important international transport cluster, will function as illustration.
Keywords: 330